SME Halal Raw Material Supply Chain Management System for White Space Resources - TENGKU MASLY MOHD GADAFI, TENGKU MUHAMMAD MUZAFFAR; RAMLI, AZIZUL AZHAR (Applied Information Technology And Computer Science, 2025)
The purpose of this project is to enhance control over halal supply chain processes for SMEs in Batu Pahat, Johor, when it comes to halal-certified chicken. Its purpose is to ensure traceability, transparency and make operations more efficient with a Halal Raw Material Supply Chain Management System online. Relying on Extreme Programming (XP), the system includes tools for inventory, halal certification monitoring and logistics. Thanks to the results, stakeholders can communicate well and complete tasks more efficiently. It allows SMEs to make their products more trusted by consumers and respond better to the needs of the market. Upcoming research may use innovative approaches such as blockchain, to boost security and traceability in the halal supply chain.